PROPOSAL OF A SOLUTION FOR WATER DESALINIZATION USING SOLAR ENERGY - Rabai, Mohamad; Nääs, Irenilza de Alencar (Revista Brasileira de Engenharia de Biossistemas, 2021)
Water is abundant on Earth, only about 2.5% is freshwater, and because most of that water is stored as glaciers or deep groundwater, only a small amount of water is easily accessible to humans and animals. This study’s motivation is to find a solution for lacking freshwater, converting brackish and seawater to potable water. The main goal was to produce potable water with high-efficiency production using solar energy. The system’s main components were the absorber plate painted black, glass cover, insulation, and vessels to collect fresh water. The absorber plate is painted black to absorb solar radiation, preventing its reflection. The plate delivers higher temperatures for saline water to be evaporated and condensed afterward. The basin liner was made of an iron sheet, and the cover is made of ordinary glass, while the basin was covered with glass using silicon rubber. We used 30-degree single slope solar to identify the efficiency of using black stone without using black stone (control). The results showed that the maximum output with black stone and without it was respectively 750 ml and 600 ml; therefore, the use of black stone can increase the productivity for the single slope solar still. Keywords: Solar collector; Potable water; Brackish water.